1988
DOI: 10.1007/bf00451286
|View full text |Cite
|
Sign up to set email alerts
|

Time estimation of depressive patients: The influence of interval content

Abstract: Duration judgements for intervals of different lengths and content were studied in depressive in-patients (n = 47) and a control sample of surgical in-patients (n = 16). As suggested by research on non-clinical subjects, tasks during the intervals influenced the depressed patients' duration judgements. Severely depressed endogenous depressives (n = 17) over-estimated time when left completely unoccupied or when attending to tasks requiring concentration. Endogenous depressives (n = 17) remitted with regard to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 15 publications
2
22
0
Order By: Relevance
“…They show that a critical cluster of decision-specific temporal inabilities is a risk factor distinguishing severely depressed patients from mildly/moderate depressed patients. A similar result was obtained by Münzel et al [88] , who found that endogenous depressives (but not neurotic/reactive depressives) selectively overestimated time intervals when required to concentrate under time pressure. These results are in principal confirmed by our study.…”
Section: Vital Retardationsupporting
confidence: 69%
See 3 more Smart Citations
“…They show that a critical cluster of decision-specific temporal inabilities is a risk factor distinguishing severely depressed patients from mildly/moderate depressed patients. A similar result was obtained by Münzel et al [88] , who found that endogenous depressives (but not neurotic/reactive depressives) selectively overestimated time intervals when required to concentrate under time pressure. These results are in principal confirmed by our study.…”
Section: Vital Retardationsupporting
confidence: 69%
“…Also, employing time production/reproduction tasks, contradictory findings have been provided [88,[91][92][93][94][95] . Thönes and Oberfeld [83] , in a recent meta-analysis, reported no significant differences between normal controls and people with depression in all-time perception tasks (estimation, production/reproduction, discrimination); they also confirmed the significance of subjective time slowness occurring in people with depression.…”
Section: Vital Retardationmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, the results of studies of time perception in individuals with depressive symptoms have been inconsistent and contradictory, probably due to the heterogeneity of the populations sampled (clinically depressed patients vs. healthy participants with depressive symptoms) and the diversity of the temporal tasks employed (Msetfi et al, 2012). Some studies have failed to find any evidence of disturbed duration judgments for different levels of depression (Bech, 1975;Hawkins, French, Crawford & Enzle, 1988;Kitamura & Kumar, 1984;Mezey & Cohen, 1961;Munzel, Gendner, Steinberg & Raith, 1988;Prabhu, Agrawal & Teja, 1969;Wyrick & Wyrick, 1997). Other studies, by contrast, have found that depressive mood disrupts time judgments by causing time distortions and/or by reducing sensitivity to time (Bschor et al, 2004;Grinker, Glucksman, Hirsch & Viseltear, 1973;Kitamura & Kumar, 1982;Kuhs, Hermann, Kammer & Tolle, 1991;Msetfi et al, 2012;Mun- , 1988;Rammsayer, 1990;Sévigny, Everett & Grondin, 2003;Tysk, 1984;Wyrick & Wyrick, 1977).…”
Section: Subjective Experience Of Time's Passage and Affective Disordersmentioning
confidence: 99%